Studi visualisasi aerodinamika model sudut kemiringan badan pelari - G. Rubiono (Dinamika Teknik Mesin, 2017)
A runner deals with several forces during running in air medium. Aerodynamics is a branch of science which studies the object behavior in air flow. This research is aimed to visualized angle body inclination of a model runner as aerodynamics study. The research is done in wind tunnel. The model use is a puppet with 30 cm height. Visualization is done by smoke method and recorded with a camera. The data is analyzed to get the curve angle of fluid flow. The analysis is done by Microsoft Visio Professional 2002 SR-1. The result shows that model runner body inclination has effect due to aerodynamics aspect. The increase of inclination angle tends to increase the curve angle of fluid flow.